2008
DOI: 10.1186/1746-1596-3-26
|View full text |Cite
|
Sign up to set email alerts
|

Is collagenase-3 (MMP-13) expression in chondrosarcoma of the jaws a true marker for tumor aggressiveness?

Abstract: Background: Matrix metalloproteinases (MMPs) play an important role in the modeling and remodeling of the extracellular matrix in both physiologic and pathologic states and thus plays an important role in tumor progression. Human collagenase-3 (MMP-13) is a member of matrix metalloproteinase family of enzymes that was originally identified in breast carcinomas and subsequently detected during fetal ossification and in arthritic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Conversely, C-20/A4 tested positive for MMP-3 unlike previously shown [Finger et al, 2004], with more modest levels of aggrecan compared to A13/BACii. The expression of MMP-3, MMP-9 and MMP-13 has been associated with chondrosarcomas [Kawashima et al, 1997;Soderstrom et al, 2001;Kuroki et al, 2002;Zyada and Shamaa, 2008], and correlates with their grading and capacity to metastasize to the lungs [Sakamoto et al, 1999;Hou et al, 2011], coincidentally, the main target for B[ ␣ ]P tumourgenesis in vivo. As some established chondrosarcoma cell lines including swarm rat chondrosarcoma [Breitkreutz et al, 1979], OUMS-27 [Kudo et al, 2007] and HCS-TG [Kudawara et al, 2004] produce col2, it may be suggested that A13/BACii is a B[ ␣ ]P-transformed chondrosarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, C-20/A4 tested positive for MMP-3 unlike previously shown [Finger et al, 2004], with more modest levels of aggrecan compared to A13/BACii. The expression of MMP-3, MMP-9 and MMP-13 has been associated with chondrosarcomas [Kawashima et al, 1997;Soderstrom et al, 2001;Kuroki et al, 2002;Zyada and Shamaa, 2008], and correlates with their grading and capacity to metastasize to the lungs [Sakamoto et al, 1999;Hou et al, 2011], coincidentally, the main target for B[ ␣ ]P tumourgenesis in vivo. As some established chondrosarcoma cell lines including swarm rat chondrosarcoma [Breitkreutz et al, 1979], OUMS-27 [Kudo et al, 2007] and HCS-TG [Kudawara et al, 2004] produce col2, it may be suggested that A13/BACii is a B[ ␣ ]P-transformed chondrosarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-13 expression has been implicated in both physiological and pathological conditions. It has been shown to be essential for normal generation of granulation tissue in mice (20), and it is expressed in various cancers (39)(40)(41)(42). MMP-13 plays predominant roles in rheumatoid arthritis and osteoarthritis, and increased expression of MMP-13 induces osteoarthritis in mice (43).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma is a type of bone cancer originating from cartilaginous tissue and is the second most common bone tumor (1). Chondrosarcomas respond poorly to radiotherapy and chemotherapy, which are the currently used treatment strategies for this malignancy, making the management of chondrosarcomas a challenge (2).…”
Section: Introductionmentioning
confidence: 99%